(untitled) (The Review of Diabetic Studies, 2025)
Background: Prostate cancer progression is characterized by extensive disruption of normal cell-cycle regulatory mechanisms and the ability of cancer cells to evade programmed cell death. These alterations lead to uncontrolled cellular proliferation, genomic instability, and resistance to therapeutic interventions. The aim of the study was to assess the effects of crude Searsia rhemanniana extracts on cell cycle progression in the human prostate cancer cell line DU145. Methods: Plant extracts were prepared using methanol, dichloromethane, and water as solvents. DU145 prostate cancer cells were seeded in 96-well plates at a concentration of 5,000 cells per well in 100 µL of growth medium and incubated overnight to promote cell adhesion. Following attachment, the cells were exposed to the respective extracts at their predetermined IC₅₀. Results: Melphalan, used as a positive control, showed the expected effects of a DNA alkylating agent by causing significant G2/M phase arrest and increased apoptosis, confirming DNA damage checkpoint activation. Among the plant extracts, the bark methanol and leaf water extracts of S. rhemanniana demonstrated the strongest cytotoxic activity, inducing apoptosis rates above 28% and 43%, respectively, without prior cell cycle arrest. In contrast, the bark and root dichloromethane (DCM) extracts caused notable accumulation of cells in early mitosis along with measurable apoptosis, indicating a distinct mechanism of action. Meanwhile, the aerial methanol extract exhibited a mechanistic profile like Melphalan, with marked G2 arrest and apoptosis, suggesting it may induce DNA damage or replication stress. Conclusion: The findings of the present study indicate that S. rhemanniana possesses a diverse array of bioactive constituents that can specifically influence the survival and behaviour of prostate cancer cells. These compounds appear to act through various molecular signalling mechanisms, suggesting their potential to modulate key cellular processes such as proliferation, apoptosis, and differentiation in a selective and targeted manner.